PENGAWASAN PENERAPAN SUMUR RESAPAN OLEH DINAS TATA RUANG DAN BANGUNAN KOTA PEKANBARU (STUDI KASUS KECAMATAN TENAYAN RAYA) - Hendry Andry (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This research was designed to determine how far the monitoring the Spatial Planning and Building Departement of Pekanbaru in the application of infiltration wells according to Perda No. 10/2006 by using three indicators, standar setting, cheking and corretive action. This research took place in the Spatial Planning and Building Departement of Pekanbaru, Tenayan Raya District. This research was descriptive survey research with quantitative method. The population consisted of two groups that the sampels are the 37 people of building owners and the 13 people of the employes. This was chosen by simple random sampling for the building owners whom did not have infiltration wells and by cencus techniques for employees. The primary and secondary data were used for data collection and analyzed by comparing problem and related theories. Bassed on the analytical techniques, the research cher assesed and conluded that the monitoring of the infiltration (Study Tenayan Raya District) quite feasible. A recommendation suggested on corretive action indicator, in order to impose sanctions buillding owner whom did not build the infiltration well according to the rules.